2019
DOI: 10.3390/w11050999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of Agricultural Water Resources Carrying Capacity in Haihe River Basin, China

Abstract: The shortage and uneven spatial and distribution of agricultural water resources has greatly restricted the sustainable development of regional society and economy. In this study, an improved five-element connection number set pair analysis model, which subdivides the same–different–opposite connection number in the set pair analysis theory to enhance the integrity and effectiveness of the original ternary connection numbers is constructed to evaluate the agricultural water resources carrying capacity (AWRCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In view of the current water shortage situation, the establishment of an optimal allocation plan to improve irrigation efficiency and ease the contradiction between supply and requirement should be suggested [46]. Therefore, how to allocate effective water resources scientifically, quantitatively, and sustainably will be the core issue of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the current water shortage situation, the establishment of an optimal allocation plan to improve irrigation efficiency and ease the contradiction between supply and requirement should be suggested [46]. Therefore, how to allocate effective water resources scientifically, quantitatively, and sustainably will be the core issue of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they took the Dianchi Lake Basin as an example in their calculation and showed that the artificial control of pollution reduction capabilities has gradually become a non-negligible part of improving the water environment carrying capacity of the basin [12]. Kang et al evaluated agricultural water resources carrying capacity from the perspective of water resources for agricultural development support [13]. Xu and Hu analyzed the relationship between the carrying capacity of water resources and the concept of sustainable development from the perspective of sustainable development.…”
Section: Integrated Water Resources Managementmentioning
confidence: 99%
“…At present, the evaluation methods of regional WRCC mainly include: fuzzy comprehensive evaluation method (Liu et al 2019;Mingxia 2020), principal component analysis method (Li & Meng 2017), system dynamics method (Ge et al 2021), grey correlation method (Ge et al 2020) and set pair analysis connection number method (Wang et al 2009;Kang et al 2019;Lele et al 2021). SPA connection number method is widely used because it can deeply analyze and quantitatively express the rich information between evaluation sample data and evaluation grades (Men & Liu 2018), which provides an effective way for evaluation of WRCC and identification of vulnerability factors.…”
Section: Introductionmentioning
confidence: 99%